Burning issues in blood pressure control - J. A. Ker; K. Outhoff (South African Family Practice)
Globally more than 1 billion people have hypertension and it is predicted that because of ageing populations and increasing sedentary lifestyles, this figure will rise to about 1.5 billion by 2025. Elevated blood pressure (BP) is the leading cause of premature death and morbidity due to stroke and ischemic heart disease. Hypertension is also a major risk factor for heart failure, atrial fibrillation, chronic kidney disease, peripheral arterial disease and cognitive decline. This article discusses the current evidencebased treatment guidelines and pressing temporal issues in optimal blood pressure control.